Cool North European summers and possible links to explosive volcanic eruptions. Issue 12 (25th June 2013) - Jones, P. D; Melvin, T. M.; Harpham, C.; Grudd, H.; Helama, S.
Abstract : [1] Exactly dated tree‐ring measurements such as ring width (TRW) and maximum latewood density (MXD), which are sensitive to summer temperatures, can provide possible routes to investigate the occurrence of hemispheric‐wide cool summers that might be linked to explosive tropical volcanic eruptions. These measurements can provide much longer records than the instrumental period, enabling much longer periods to be assessed and offers the potential to look at much larger eruptions than recorded over the last 200 years. This paper looks at TRW evidence from Northern Fennoscandia extending over the last 7500 years, using two independently produced chronologies from northern Sweden and northern Finland. TRW is less responsive than MXD to cool summer temperatures, but MXD is only available for the last 2000 years. Additionally, looking at a relatively small location, compared to the Northern Hemisphere average, adds considerable noise. Progress in this area is likely to be made by developing more millennial‐long TRW series across northern high latitudes or being able to develop MXD series from the sub‐fossil material, which comprises most of the samples prior to the last 1000 years. The three most extreme negative values for the region for the last 2000 years are 1601, 542, and 1837, although the latter is not extreme in a long instrumental record for the region. The most extreme year of all occurred in 330BC. Of the 20 most extreme negative years, nine occurred during the AD years with the remaining 11 occurring during the prior 5500 years. Key Points: Use of tree‐ring widths to look at past summers Link of cool summers to explosive volcanic eruptions Ring Width response versus density response